The Political Consequences of National Crisis Management: Micro-Level Evidence from German Voters during the 2008/09 Global Economic Crisis. Issue 1 (2nd January 2016) - Goerres, Achim; Walter, Stefanie
Abstract : How does national crisis management affect the electoral fortunes of coalition governments? Drawing on micro-level data from just before the 2009 federal elections in Germany, this article investigates how voters' evaluation of specific policies against the global financial crisis affected approval of and voting intentions for the then-governing grand coalition. We find that voters in favour of the two most prominent anti-crisis policies, the car-scrap bonus and the public guarantee for banks, were more likely to approve of and to vote for the two incumbent parties. These evaluations of specific policies influenced individuals' vote choice in addition to their assessments of the economic situation more generally and in addition to party identification. This suggests that even in the greatest economic turmoil with blurred political responsibilities, government parties can win or lose voters through the implementation of specific economic policies.